The Politics of Masculinity in Tony Gould’s Imperial Warriors: Britain and the Gurkhas - Rai, Ram Prasad (The Outlook: Journal of English Studies, 2021)
The main concern of this paper is to study on masculinity and more importantly the hyper masculinity of the Gurkhas in Imperial Warriors: Britain and the Gurkhas by Tony Gould. The writer describes the courage with discipline and dedication, the Gurkhas had while fighting for Nepal, their homeland during the Anglo-Nepal War (1814-1816) and for Britain in the First and Second World Wars, following the other wars and confrontations in many parts of the world. Despite a lot of hardships and pain in wars, they never showed their back to the enemies, but kept Britain’s imperial image always high with victories. They received Victoria Crosses along with other bravery medals. As a masculinity, the hegemonic masculinity is obviously present in the book since the high ranked British Officers are in the position to lead the Gurkha soldiers. However, the masculinity here is associated with the extreme level of bravery and that is the hyper-masculinity of the Gurkhas. Since this is a qualitative research work, the researcher has consulted various books, reviews and journal articles related to the Gurkhas. It is a new concept in the study of the Gurkhas in the particular book by Gould. So, it will certainly be a new insight for the future researchers in the related area.